ASSESSMENT OF MECHANICAL AND MANUAL SUTURE IN THE SURGICAL TREATMENT OF THE PHARYNGOESOPHAGEAL DIVERTICULUM - AQUINO,José Luis Braga de (2015)
Background: The occurrence of the pharyngoesophageal, or Zenker diverticulum is not frequent in the national scenario, and the technique of the diverticulectomy with cricomyotomy in medium and great dimension diverticula is still the most indicated. Because the resection of the diverticulum requires the suture of the pharynx, dehiscence can occur, thereafter delaying swallowing. Hence, the idea is to accomplish this surgical procedure, comparing the manual and mechanical suture, in order to evaluate the real benefit of the mechanical technique. Aim: To evaluate the results of the pharyngoesophageal diverticulectomy with cricomyotomy using manual and mechanical suture with regard to local and systemic complications. Method: Fifty-seven patients with pharyngoesophageal diverticula diagnosed through high digestive endoscopy and pharyngeal esophagogram were studied. The applied surgical technique was diverticulectomy with myotomy of the cricopharyngeal muscle, done in 24 patients (42.2%) the mechanical suture (group A) with the mechanical linear suture device and in 33 (57.8%) a manual closure of the pharynx (group B). Results: In the postoperative period, one patient of group A (4.1%) presented fistula caused by dehiscence of the pharyngeal suture, and three of group B (15.1%) presented the same complication, with a good outcome using a conservative treatment. In the same group, three patients (9.0%) presented stenosis of the suture of the pharynx, with good outcome and with endoscopic dilatations, and no patient from group A presented such complication. Lung infection was present in five patients, being two (8.3%) of group A and three (9.0%) on B, having good outcomes after specific treatment. In the late review, done with 43 patients (94.4%) of group A and 22 (88.0%) on B, the patients declared to be pleased with the surgical procedure, because they were able to regain normal swallowing. Conclusion: The diverticulectomy with myotomy and pharyngeal closure using mechanical suture was proven appropriate, for having restored regular swallowing in most of the patients, and the mechanical closure of the pharynx proved to be more effective in comparison to the manual one, because it provided a lower index of local post-surgical complications.